2008
DOI: 10.1007/s12103-008-9042-2
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense out of Nonsense: The Deconstruction of State-Level Sex Offender Residence Restrictions

Abstract: Releasing a sex offender from prison or placing the offender on community-based sanctions, only to have the offender commit a new sex crime, is a policy-maker's worst nightmare. Fueled by misperceptions and public fear, sex offender laws have developed piecemeal and without rigorous empirical insight and testing. While policies and practices are well-intended, they are unlikely to resolve the very real social problem of sexual violence and may inadvertently increase victimization. Such is the possibility with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 25 publications
3
122
1
Order By: Relevance
“…Many studies have concluded that residency restrictions have no effect of lowering sexual recidivism rates (Durling, 2006;Levenson, 2008;Levenson, 2010;Meloy, Miller & Curtis, 2008;Nobles, Levenson & Youstin, 2012;Tewksbury, 2007;Walker, 2007;& Wright, 2015). These studies also point out that while residency restrictions prohibit a sex offender from living in certain areas, they cannot legally prohibit an individual from sitting across the street near such areas.…”
Section: Residency Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have concluded that residency restrictions have no effect of lowering sexual recidivism rates (Durling, 2006;Levenson, 2008;Levenson, 2010;Meloy, Miller & Curtis, 2008;Nobles, Levenson & Youstin, 2012;Tewksbury, 2007;Walker, 2007;& Wright, 2015). These studies also point out that while residency restrictions prohibit a sex offender from living in certain areas, they cannot legally prohibit an individual from sitting across the street near such areas.…”
Section: Residency Restrictionsmentioning
confidence: 99%
“…When looking at the research, we can see that many of these restrictions do more harm than good in most situations. Residency restrictions have shown to be ineffective at reducing sexual recidivism rates (Durling, 2006;Levenson, 2008;Levenson, 2010;Meloy, Miller & Curtis, 2008;Nobles, Levenson & Youstin, 2012;Tewksbury, 2007;Walker, 2007;& Wright, 2015), but introduce other consequences such as homelessness and severed bonds between family members and friends. Residency guidelines can essentially banish offenders out in to rural areas.…”
Section: Future Direction Policy Changesmentioning
confidence: 99%
“…In the past 20 years, sex offender residence restrictions (SORR) have been widely deployed as a means to manage the recidivism risk of sex offenders in the community (Levenson and Cotter, 2005;Meloy, Miller, and Curtis, 2008). Residence restrictions aim to impede opportunities for reoffending among known, registered sex offenders by regulating their residential proximity to areas where potential child victims congregate.…”
Section: Examining the Correlates Of Sex Offender Residence Restrictimentioning
confidence: 99%
“…Although there is wide variation in statewide SORR laws nationally (Meloy et al, 2008;Mancini et al, 2013), the study states are two of 13 states with boundary zones in the interval of 1,000 to 1,499ft, which is the most common boundary interval out of the 32 states with statewide policies .…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation